Inventory management in gold mining industry: opportunities and challenges - Umetaliev, Chingiz (Advanced Logistic Systems - Theory and Practice, 2026)
Inventory management in gold mining represents a strategic and complex function that influences equipment availability, maintenance cost efficiency, and overall operational continuity. Gold mining enterprises rely on extensive inventories supporting a large, diverse set of machinery and equipment required for extraction, haulage, processing, and maintenance. Long-operating mines often accumulate more than 100,000 stock-keeping units (SKUs), driven by continuous technological renewal, changes in machinery suppliers, and evolving operational demands. These factors create significant challenges in forecasting, procurement, and stock optimization. This article examines the key inventory management challenges specific to gold mining enterprises and integrates insights from research articles in spare-parts inventory, supply chain management, and mining logistics. Particular emphasis is placed on intermittent demand, rotables management, long and uncertain lead times, supplier constraints, equipment obsolescence, and the increasing need for digital solutions based on condition monitoring and predictive maintenance. The study provides a structured overview of the problem space and highlights emerging approaches that combine data analytics, risk-based classification, and integrated maintenance–inventory planning.